Bonding mechanisms of graphene on metal surfaces - Kozlov, Sergey M.; Vines, Francesc; Görling, Andreas (Journal of Physical Chemistry C, 2012)
The basic bonding mechanisms of graphene on transition-metal surfaces leading to chemisorption and physisorption are identified and studied in the example of graphene adsorption on Ni(111) by means of density functional theory at the general gradient approximation level with semiempirical corrections for dispersive interactions. In the more stable chemisorbed graphene, relatively strong Pauli repulsion between graphene and the substrate is compensated by donation/back-donation bonding of the same magnitude. In this case, the electronic interactions with the substrate significantly perturb the electronic structure of graphene, but the adsorption energy is still dominated by van der Waals (vdW) interactions. In physisorbed graphene, weak Pauli repulsion equilibrates the vdW attraction without affecting the electronic structure of graphene. The relative stability of physisorbed and chemisorbed graphene is shown to be changed by carbidic C impurities in the subsurface region. © 2012 American Chemical Society.